2009
DOI: 10.1590/s0100-736x2009000700012
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de sensibilidade microbiana in vitro de linhagens de Staphylococcus spp. isoladas de vacas com mastite subclínica

Abstract: Objetivou-se com este estudo avaliar a sensibilidade antimicrobiana in vitro de 291 isolados de Staphylococcus spp. recuperados de amostras de leite de vacas com mastite subclínica, em 15 propriedades rurais localizadas na Região Metropolitana do Recife (A), Agreste (B) e Zona da Mata (C) do estado de Pernambuco. Dos 291 isolados, 170(58,4%) foram classificados como Staphylococcus coagulase negativa (SCN), 84(28,9%) como Staphylococcus aureus e 37(12,7%) como Staphylococcus coagulase positiva (SCP). Para o est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
15

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 14 publications
2
9
0
15
Order By: Relevance
“…Even the resistance to penicillin, which is highly prevalent among S. aureus strains in Brazilian herds (Medeiros et al 2009, Silva et al 2012, was found in only 18.2% of strains. Among the sampled farms, only clinical mastitis cases were treated with antimicrobials and no susceptibility test was performed.…”
Section: Discussionmentioning
confidence: 98%
“…Even the resistance to penicillin, which is highly prevalent among S. aureus strains in Brazilian herds (Medeiros et al 2009, Silva et al 2012, was found in only 18.2% of strains. Among the sampled farms, only clinical mastitis cases were treated with antimicrobials and no susceptibility test was performed.…”
Section: Discussionmentioning
confidence: 98%
“…Estas espécies isoladas nesse estudo são amplamente relatadas como causadoras de mastite em fêmeas bubalinas no Brasil (Cunha et al 2006) e no mundo (Saini et al 1994, Lazzari et al 2002. Na espécie bovina, também observou-se maior frequência de SCN, corroborando com vários estudos realizados no Brasil (Almeida et al 2005, Medeiros et al 2009, Oliveira et al 2011 e no mundo (Waage et al 1999, De Vliegher et al 2012. A maior prevalência de SCN neste estudo pode estar relacionada com as precárias condições de higiene nos locais de ordenha e das mãos do ordenhador.…”
Section: Discussão E Conclusõesunclassified
“…Observa-se que assim como a tetraciclina, a ampicilina apresentou uma melhor atuação sobre as bactérias isoladas de mastite bubalina. Essa diferença de atuação pode ser provocada pela ampla utilização desses fármacos em infecções presentes em bovinos, resultando no uso indiscriminado do medicamento e contribuindo para seleção de cepas resistentes (Medeiros et al 2009). Além disso, tem-se a eϐiciência da resistência plasmidial por meio da transferência de genes, resultando quase sempre, na produção de enzimas.…”
Section: Discussão E Conclusõesunclassified
“…On the other hand, the microorganisms showed susceptibility percentages above 80% for the rest of the drugs evaluated, especially for cephalexin, gentamicin and enrofloxacin. Other authors (Nader Filho et al 2007, Medeiros et al 2009) described similar findings, suggesting that these antimicrobial agents could provide good in vivo effectiveness in the treatment of staphylococcus mastitis. Furthermore, susceptibility to all the active ingredients tested was seen in 28% of the isolates of this study; this situation was described in 37.8% of the Staphylococcus spp.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, susceptibility to all the active ingredients tested was seen in 28% of the isolates of this study; this situation was described in 37.8% of the Staphylococcus spp. of mastitis milk analyzed by Medeiros et al (2009).…”
Section: Discussionmentioning
confidence: 99%